2002
DOI: 10.1159/000063358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roxithromycin on the Production of Lipase and Neutrophil Chemotactic Factor by <i>Propionibacterium acnes</i>

Abstract: Background: The macrolide antibiotic roxithromycin is effective against acne associated with inflammation, but the mechanism by which this is achieved has not been clarified. Objective: We studied the effects of roxithromycin on the production of lipase and neutrophil chemotactic factor by Propionibacterium acnes in vitro. Results: Roxithromycin significantly inhibited the production of lipase and neutrophil chemotactic factor by P. acnes at a concentration one eighth of the MIC, at which the growth curve of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…RXM shows a potent antibacterial activity against Propionibacterium acnes, and is clinically applied for acne [33,34]. Recent study revealed that RXM has an anti-inflammatory effect by inhibiting neutrophil-derived oxygen radical generation [11].…”
Section: Discussionmentioning
confidence: 99%
“…RXM shows a potent antibacterial activity against Propionibacterium acnes, and is clinically applied for acne [33,34]. Recent study revealed that RXM has an anti-inflammatory effect by inhibiting neutrophil-derived oxygen radical generation [11].…”
Section: Discussionmentioning
confidence: 99%
“…So far, antibiotic agent, roxithromycin, has been frequently used for acne treatment. This agent significantly inhibits lipase activity of P. acnes and this is, in part, associated with clinical improvement (Akamatsu et al, 2002). P. acnes lipases may be potential targets for the development of effective drugs or vaccines against P. acnes-associated diseases.…”
Section: Genome and Proteome Of P Acnesmentioning
confidence: 99%
“…The latter is considered to trigger the inflammatory cascade [36]. This hypothesis has gained support because several anti-acne drugs have been shown to inhibit the generation or activity of chemotactic factors or the release of reactive oxygen species [37]. In addition, linoleic acid, which is deficient in acne comedones, inhibits neutrophil oxygen metabolism and phagocytosis.…”
Section: Therapeutic Targets and Acne Drugsmentioning
confidence: 99%
“…It accumulates at therapeutic levels in the pilosebaceous system [90]and exhibits an interesting spectrum of effects, namely direct anti-inflammatory and anti-androgenic activities. It significantly inhibits the production of lipase and neutrophil chemotactic factor by P. acnes as well as of P. acnes -induced NF-kB activation at concentrations much lower than the MIC at which the growth curve of P. acnes is not affected [34, 91]. In addition, roxithromycin was found to serve as anti-androgen only in the hypersensitive state to androgens, but not in the physiological state through modulating end-organ hypersensitive condition to androgens [92].…”
Section: New Developments and Future Trendsmentioning
confidence: 99%